Neurotrophic Keratitis. Etiology, Pathogenesis, Clinical Manifestations. Review. Part 2 - E. A. Kasparova; N. R. Marchenko (Oftalʹmologiâ)
Neurotrophic keratitis (neurotrophic keratopathy) (NTC) is a degenerative disease of the cornea accompanied with neurogenic inflammation. It is caused by a loss of sensitive innervation of the trigeminal nerve. Therapeutic measures are mainly reduced to maintenance therapy (antiseptics, artificial tears, corneal protectors), which does not affect the cause of the disease. The most affordable and updated therapy is the long-term topical use of auto- or heterologous serum. Recently developed specific approaches to the treatment of NTK — local therapy with recombinant nerve growth factor Cenegermin and corneal neurotization are aimed at the pathogenetic links of the disease and can restore the innervation and sensitivity of the cornea.